(untitled) - Goldhil DVD (Firm) (Camarillo, CA., 2005)
With these proven methods you can boost scores in the Math sections, from Geometry to Algebra I & II to quadratic equations. Topics covered: decimal problems, mode & median, algebra & geometry, ratios & square roots, and much, much more.
Keywords: Hình học,Geometry; Nghiên cứu và giảng dạy,Study and teaching